Cerebral echinococcosis multilocularis. Case report - (:unkn) unknown (My University, 1991)
Cerebral occurrence of Echinococcus multilocularis is very rare and there is no widely accepted therapeutical method. In this report we present a case with an intracranial mass lesion and a palpable hepatic mass, which appeared to be due to Echinococcus multilocularis in the histopathological examination.
Keywords: Adult; Female; Humans; Tomography, X-Ray Computed; Brain; Brain Diseases; Echinococcosis